Control Algorithm for a Dynamic Pricing Management of Electrical Energy - Acosta-Barbosa, K (Institute of Electrical and Electronics Engineers Inc., 2019)
This article presents the design of a control algorithm for the management of the purchase / sale of electrical energy by generators distributed in a distribution system with dynamic energy charging. In particular, an algorithm based on dynamic programming is implemented to maximize the income of each user daily, considering a pricing model proposed earlier in the literature. The results of the controller application, obtained by simulations, are analyzed to assess its impact on the demand of the distribution system. © 2019 IEEE.